The Dark Triad and the PID-5 Maladaptive Personality Traits: Accuracy, Confidence and Response Bias in Judgments of Veracity - Wissing, Benno G.; Reinhard, Marc-André (Frontiers in Psychology, 2017)
The Dark Triad traits – narcissism, Machiavellianism and psychopathy – have been found to be associated with intra- or interpersonal deception production frequency. This cross-sectional study (N = 207) investigated if the Dark Triad traits are also associated with deception detection accuracy, as implicated by the recent conception of a deception-general ability. To investigate associations between maladaptive personality space and deception, the PID-5 maladaptive personality traits were included to investigate if besides Machiavellianism, Detachment is negatively associated with response bias. Finally, associations between the Dark Triad traits, Antagonism, Negative Affectivity and confidence judgments were investigated. Participants watched videos of lying vs. truth-telling senders and judged the truthfulness of the statements. None of the Dark Triad traits was found to be associated with the ability to detect deception. Detachment was negatively associated with response bias. Psychopathy was associated with global confidence judgments. The results provide additional support that dark and maladaptive personality traits are associated with judgmental biases but not with accuracy in deception detection. The internal consistencies of 4 of the 8 subscales of the used personality short scales were only low and nearly sufficient (αs = .65–.69).